A formação inicial em educação física na UFSM: a lei 10.639/03 em uma abordagem intercultural - Messias, Andressa Rodrigues (2019)
The present study analyzed the initial training in Physical Education, specifically the undergraduate course at the Federal University of Santa Maria (UFSM). The research proposal aims to understand, taking as reference Law 10.639 / 03, as the initial training in Physical Education Degree of UFSM, is manifesting the necessary bases to face the challenge of interculturality in the educational process. With emphasis on cultural diversity, particularly ethnic-racial diversity, an important aspect of teacher education, which imposes on educators the approach of African, Afro- Brazilian and indigenous history and culture in primary and secondary education. It adopts the perspective of historical-dialectical materialism, as a theoretical and methodological reference and as techniques of analysis, bibliographical revision and documentary analysis. At the end of the study, we find that today Law 10.639 / 03 is not yet effectively fulfilled. Failure to comply with this law corroborates the history of Africa not counted in Brazil, which means that we do not have black references in the sciences; in the arts; in politics and in many other areas of knowledge recorded in textbooks used in primary and higher education schools. This reality further reinforces our culture of discrimination and ethnic racial prejudice.